Analisis Optimalisasi Tekanan Minyak Lumas Terhadap Kinerja Mesin Induk di KM. Kendhaga Nusantara 04 - Dari , Riris Anandita Wulan; Kristiyono , Antonius Edy; Pribadi , Teguh; Robbi, Shofa Dai; Prawoto, Agus (Universitas Pahlawan Tuanku Tambusai, 2025)
The main engine serves as the primary driving force and plays a crucial role in ensuring the smooth operation of the ship. An important aspect of maintaining the optimal performance of the main engine is preserving the quality of the lubricating oil and ensuring that its specifications comply with the manufacturer's standards.This study aims to identify various factors that can cause suboptimal lubricating oil pressure and explore steps that can be taken to improve and optimize these conditions. By understanding the underlying causes and potential solutions, it is hoped that the performance of the main engine can be enhanced, thereby supporting the overall operational efficiency and reliability of the ship.This study employs qualitative methods. Data sources were obtained through direct observation, interviews with the engine operator, and document analysis. The findings indicate that factors such as dirty filters, oil quality, and pipeline conditions affect lubricating oil pressure. Optimization efforts include periodic inspections of oil quality and regular maintenance of the lubrication system.The study highlights the importance of proper maintenance and quality supervision of the lubrication system to prevent a decline in engine performance.